2014
DOI: 10.1080/17470218.2013.838281
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Elemental Processing in a High Schizotypy Population: Relation to Cognitive Deficits

Abstract: The cognitive deficits observed in schizophrenia have been characterized as a failure to utilize task-setting information to guide behaviour, especially in situations in which there is response conflict. Recently, we have provided support for this account; high schizotypy individuals demonstrated inferior biconditional discrimination performance compared to low scorers, but were not impaired on a simple discrimination that did not require the use of task-setting cues. These results may, however, also be explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
2
4
0
1
Order By: Relevance
“…Although novel, this view is broadly consistent with previous finding of altered perceptual strategies in schizophrenia, a clinical condition characterized by social anhedonia (Blanchard, Horan, & Brown, 2001), such that schizophrenia patients as compared to normal people manifested a restricted visual scanpath characterized by an overreliance on sequential or featural processing (Toh, Rossell, & Castle, 2011). In support of our explanation, previous studies found that healthy individuals high in introvertive anhedonia exhibited an extreme bias toward elemental, instead of configural, processing of information conjunctions (Haddon et al, 2011(Haddon et al, , 2014.…”
Section: F I G U R Esupporting
confidence: 91%
See 1 more Smart Citation
“…Although novel, this view is broadly consistent with previous finding of altered perceptual strategies in schizophrenia, a clinical condition characterized by social anhedonia (Blanchard, Horan, & Brown, 2001), such that schizophrenia patients as compared to normal people manifested a restricted visual scanpath characterized by an overreliance on sequential or featural processing (Toh, Rossell, & Castle, 2011). In support of our explanation, previous studies found that healthy individuals high in introvertive anhedonia exhibited an extreme bias toward elemental, instead of configural, processing of information conjunctions (Haddon et al, 2011(Haddon et al, , 2014.…”
Section: F I G U R Esupporting
confidence: 91%
“…Specifically, happy expression processing depends more on configural information (the relations among facial features), whereas sad expression processing relies on featural information (the circumscribed face components such as the mouth) to a greater extent. On the other hand, previous studies have demonstrated that introvertive anhedonia, which reflects traits such as a lack of enjoyment from social pleasure and the avoidance of social intimacy (Mason & Claridge, 2006), may reflect a bias toward featural, as opposed to configural, approach to stimulus processing (Haddon et al., 2011, 2014). However, the possibility of perceptual deficits of emotional facial expression processing in social anhedonia has not yet been directly assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Turning to schizotypy, some studies in healthy participants have provided evidence for a relationship between aberrant salience and the positive dimension of schizotypy (Evans et al ., ; Gray, Fernandez, Williams, Ruddle, & Snowden, ; Lipp, Siddle, & Arnold, ), while others (like the current experiments) have found a relationship with the negative dimension (Haddon et al ., , ; Haselgrove & Evans, ; Moran et al ., ), and Le Pelley, Schmidt‐Hansen et al . () found trend‐level evidence implicating all four O‐LIFE dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that when stimuli of mismatched salience were presented in compound, the high salience stimulus is over-represented, impairing acquisition. Although there has been considerable exploration of the factors that influence configural learning, including stimulus properties and training (for review, see Melchers, Shanks, & Lachnit, 2008) and individual differences (Byrom & Murphy, 2014, 2016Haddon et al, 2014), the influence of relative stimulus salience has received less attention. This is curious, as beyond the laboratory, the stimulus configurations routinely encountered do not consist of equally associable components.…”
Section: Discussionmentioning
confidence: 99%